Research and Practice of Big Data Platform of Games - Yang Su; Xiaojun Liu; Yong Tang; Yang Huang (Dianxin kexue)
Based on the game platform data processing needs,the diversified mix of large data processing architecture was built based on distributed+relational data,for high-value-density structured data using relational data processing;lots of disorderly unstructured data processing was using a distributed mechanism. Two types of data to achieve the orderly were unified handed over to traditional relational database model to build relationships and showed that could be achieved through efficient handling of business analysis data, but also to meet the scale of disorderly log data processing requirements. The overall architecture, the main features and key technologies were analyzed, so as reference was provided for other business data analysis platform for large construction and renovation.